(untitled) (Research, Society and Development, 2021)
This research aimed to assess the effect of aluminum oxide sandblasting and discs on the bond strength of metal brackets rebonded on artificially eroded enamel. Fifty-four bovine incisors were divided into groups: Control (Artificial Saliva), AlOx (Aluminum oxide sandblasting), and SL (Aluminum oxide discs). They had their enamel surface flattened with Al2O3 discs and a metallographic polisher, then Knoop microhardness was assessed. AlOx and SL specimens were eroded with Coca-Cola™ for 1 minute, 3 times a day for 7 days. Metal brackets were bonded to the tooth. Shear strength was measured by an EMIC universal testing machine (0.5 mm/min). The Adhesive Remnant Index (ARI) was performed after shearing through magnifying glass (10X). Kolmogorov-Smirnov, Levene, homoscedasticity and ANOVA tests were applied to assess microhardness and shear strength (p=0.163). All groups presented shear bond strength with no significant differences. The ARI showed statistically significant difference between the groups. The prevalence for the control group was ARI 3. However for AlOx and SL, ARI 1 and 2 prevailed. The aluminum oxide sandblasting and aluminum oxide discs did not positively increase the bond strength of brackets when bonded to artificially eroded enamel. The ARI indicated that eroded teeth present higher resin adhesion to enamel.